O avanço do agronegócio e o índice de crescimento sustentável dos municípios do Mato Grosso - Ferraz, Maurício Munhoz (2020)
The objective of this academic work is to analyze the impacts of agribusiness on the life of the population of Mato Grosso based on the Index of Sustainable Growth of Municipalities (ICSM), having as variables: GDP per capita, Percentage of families receiving the “Bolsa Família” (government aid for low-income families), Average salary, Public service participation in GDP, Basic education index, Infant mortality, Heat sources, Forest area per km2. The 2017 Agricultural Census confirms the expansion of temporary crops, the basis of agribusiness, and the process of accumulating land in the State, which is linked to the tax facility given to large-scale agriculture, such as the total exemption from taxes on sales the primary products for export, according to the Kandir Law, and the low internal tax burden applied on grain production and the livestock sector, by the government of Mato Grosso. By adopting the sustainable growth index of the municipalities, ICSM, as a tool to analyze the impact of advancing agribusiness on people's quality of life, the study concludes that, despite agribusiness for over twenty years, the predominant economic model in the State, the income, social and environmental indicators of their municipalities are bad, even if those large grain producing municipalities have good income levels. In theoretical terms, the research will follow the base of authors who discuss the process of capitalist accumulation. In methodological terms, it is a qualitative research, with techniques of quantitative approach, with the period from 2000 to 2019 as its time frame.